Quality of life and associated factors in colorectal cancer patients with colostomy at King Chulalongkorn Memorial Hospital. - Atthaphinan , C.; Lueboonthavatchai, P. (Chulalongkorn Medical Journal, 2023)
Background : Patients with colorectal cancer that have undertaken surgery with opening colostomy, causing structural and functional changes in bowel movement. However, studies on the quality of life and associated factors with in colorectal cancer an artificial limit. Objective : To identify the quality of life and its associated factors in colorectal cancer patients with colostomy at the Outpatient Department, Surgical Clinic, King Chulalongkorn Memorial Hospital. Methods : Ninety colorectal cancer patients, were recruited from the Outpatient Department, Surgical Clinic, King Chulalongkorn Memorial Hospital from January 2016 to March 2016. All subjects completed eight questionnaire: 1) Demographic data and social information form; 2) Health information questionnaire; 3) Knowledge about colostomy questionnaire; 4) Sexual relationship questionnaire; 5) World Health Organization’s Quality of life Brief – Thai questionnaire (WHOQOL-BREF-THAI); 6) Social support questionnaire; 7) Thai Hospital Anxiety and Depression Scale (Thai HADS); 8) Thai interpersonal questionnaire. The associated factors of quality of life in the patients were analyzed by chi-square test; logistic regression was used to identify the predictor of good quality of life. Result : Most of colorectal cancer patients with colostomy at King Chulalongkorn Memorial Hospital (67.8%) had moderate level of quality of life. Factors associated with their quality of life were marital status, education level above bachelor degree, concerns for health and welfare, no history of smoking and alcoholic drinking, having good interpersonal functioning, no anxiety and no depression. Accordingly the logistic regression showed the predictors of good quality of life were having good interpersonal functioning, no smoking history, married, having education level higher than bachelor degree and welfare. Conclusion : Most colorectal cancer patients with colostomy at King Chulalongkorn Memorial Hospital had moderate level of quality of life. Good interpersonal functioning, no history of smoking, married, having education level higher than bachelor degree and welfare may help improve the quality of life.